2019
DOI: 10.1002/jcb.28351
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of matrix metalloproteinase‐7 and matrix metalloproteinase‐15 in acute myeloid leukemia

Abstract: Matrix metalloproteinases (MMPs), a family of zinc-dependent endopeptidases, are involved in a variety of physiological and pathological processes. We analyzed 11 data sets from Gene Expression Omnibus Database and found that MMP7 and MMP15 were highly expressed in multiple carcinomas. GSE13204 showed that MMP7 and MMP15 were overexpressed in acute myeloid leukemia (AML) patients.The Cancer Genome Atlas data set exhibited that high expression of MMP7 or MMP15 in bone marrow (BM) of AML patients predicted poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Interestingly, we have also identified the matrix metalloproteinase Mmp2, an extracellular protease responsible for extracellular matrix (ECM) degradation. Its mammalian counterpart MMP15 (aka MT2-MMP) is apparently expressed in several myeloid cell lines and in AML samples, which suggests a contribution to the invasiveness properties of NA9-mediated leukemia [88,89].…”
Section: A Role In Cell Polarity / Basement Membrane Organizationmentioning
confidence: 99%
“…Interestingly, we have also identified the matrix metalloproteinase Mmp2, an extracellular protease responsible for extracellular matrix (ECM) degradation. Its mammalian counterpart MMP15 (aka MT2-MMP) is apparently expressed in several myeloid cell lines and in AML samples, which suggests a contribution to the invasiveness properties of NA9-mediated leukemia [88,89].…”
Section: A Role In Cell Polarity / Basement Membrane Organizationmentioning
confidence: 99%
“…It was reported that MMP14 is the target of BCR-ABL/ABL interactor 1 (Abi 1) signaling, and induces increased motility and invasiveness leukemic cells [ 78 ]. MMP15 is highly expressed in AML patients and was correlated with poor overall survival [ 79 ]. Downregulation of MMP14 and MMP15 by 8-OHD may indicate that it possesses anti-metastatic activity ( Figure 4 c,d).…”
Section: Resultsmentioning
confidence: 99%
“…MMP-7 was found to be upregulated in patients with AML, especially in patients who had relapsed (36). Wu et al also suggested that higher levels of expression of MMP7 can predict poor OS in AML (37). PDCD1 (PD-1, Programmed Cell Death 1 Protein) has been found to be highly expressed in many cancers and was found to be responsible for the escaping of cancer cells from immunosurveillance.…”
Section: Discussionmentioning
confidence: 99%